Role of the oceans in the climatic variability of the African monsoon - (:unkn) unknown (My University, 2008)
The oceans explain an important part of the variability of monsoon rainfall overWest Africa. What are the physical processes of those ocean–atmosphere interactions? How are they simulated by climate models? Both issues are addressed, by considering the interannual and decadal time-scales separately, and comparing the simulations performed for the Intergovernmental Panel on Climate Change (IPCC) to the 20th Century observation record. At the interannual time-scale, sea surface temperature anomalies in the equatorial Pacific, the Gulf of Guinea, and the Mediterranean, are statistically linked to the West African monsoon rainfall. The stationnarity of those links is assessed over the 20th Century. The physical processes are then studied in the atmospheric reanalyses and in the IPCC coupled simulations. To understand the behaviour of the Centre national de recherches météorologiques (CNRM) model, various sensitivity experiments are carried out, with a reanalyzed wind-stress prescribed to the ocean model, over the tropical Pacific or over the global ocean. An atmospheric simulation with prescribed sea surface temperatures is also used, to discuss the role of the ocean–atmosphere coupling. Given the seasonality of the West African monsoon, attention has to be paid to the phaselocking of the oceanic variability. In the coupled models, the biases of the El Niño–Southern Oscillation (ENSO) and of the Atlantic Niño lead indeed to ocean–monsoon interactions that are different from those observed. A better understanding and simulation of the oceanic variability and its influences could in fine enhance the seasonal forecasting skills over West Africa
Keywords: African Research